Aggregation Induced Emission (AIE)‐Active Poly(acrylates) for Electrofluorochromic Detection of Nitroaromatic Compounds. Issue 11 (15th September 2022) - Chua, Ming Hui; Chin, Kang Le Osmund; Ang, Shi Jun; Soo, Xiang Yun Debbie; Png, Zhuang Mao; Zhu, Qiang; Xu, Jianwei
Abstract: Two aggregation induced emission (AIE)‐active poly(acrylates) bearing triphenylvinyl‐functionalized phenylcarbazole and triphenylamine pendants, respectively, were synthesized. Their fluorescence response to nitroaromatics and electrofluorochromic (EFC) properties were studied, whereby both the presence of nitroaromatics and applied voltages led to fluorescence quenching. In a very first attempt to perform EFC detection of nitroaromatics, it was surprisingly found that after initial fluorescence quenching, the presence of nitroaromatics unexpectedly turned on fluorescence at high applied voltages (>+1.0 V), demonstrating a promising approach for the EFC detection of nitroaromatic explosives. Abstract : Explosive detection : Novel AIE‐active poly(acrylates) were prepared for both electrofluorochromic applications and nitroaromatics detection. An unusual fluorescence turn‐on was however observed during an attempted electrofluorochromic sensing of nitroaromatic compounds performed with the triphenylamine‐based poly(acrylate), opening up possibilities and future opportunities for the development in EFC‐sensing of nitroaromatic explosives based on this phenomenon.